O direito fundamental do consumidor na jurisprudência do Superior Tribunal de Justiça - Araújo, Juliana Sampaio de (2017)
The current dissertation has as a main objective to analyze the fundamental right of the consumer on the jurisprudence of the Superior Court of Justice (STJ). For the purpose, the questions surrounding the current capitalist and consumer society are researched, as well as a brief analysis of the connection between the consumer and the capitalist system of production. Still, with the examination of the judicial bias, some decisions of the STJ are observed in the treatment of the matter, as well as some controversial precedents of the same court on the consumer issue. It is important to highlight the importance of viewing the consumer, his or her fundamental right, both in relations with the State and in relation to individuals. This study also examines the National Consumer relations, implemented in Brazilian law, as well as the judicial and administrative protection of consumer relations, in its dissonant aspects with the protection of other branches of civil and procedural law. The methodology used in this dissertation is based on bibliographical research, using books, articles, online publications, and legislation on the subject in question. As far as nature is concerned, research is qualitative ,and of the purpose, exploratory and descriptive. Consumers today are seen as the most fragile part of the consumer relationship, where it is often at the mercy of companies that do not have adequate information, causing the consumer to lack the resources to complain. The right of the consumer as a fundamental right entails a series of changes, both in judicial and administrative protection, both from a procedural perspective and in eminently private matters. In the midst of so many innovations, the jurisprudence of the STJ is still a bit hesitant in dealing with these issues, either by duly applying the Consumer Protection Code (CDC) or by making its devices dead, in some of its judgments or in Some of its overviews. Likewise, throughout the dissertation, decisions issued by the STJ that endorse the consumer's problem are pointed out, giving it an eminently protective bias.